Screening manual and office workers for risk of long-term sickness absence: cut-off points for the Work Ability Index - Schouten, Lianne S; Joling, Catelijne I; van der Gulden, Joost WJ; Heymans, Martijn W; Bültmann, Ute; Roelen, Corné AM (Scandinavian Journal of Work, Environment & Health, 2015)
' ' OBJECTIVES ': 'The aim of this study was to investigate the Work Ability Index (WAI) as a tool to screen for risk of different durations of long-term sickness absence (LTSA) among manual and office workers. ' ' METHODS ': 'The prospective study comprised a cohort of 3049 (1710 manual and 1339 office) workers participating in occupational health surveys between 2010–2012. The survey date was set as baseline and incident LTSA episodes of different duration (>14, >28, >42, >60, and >90 days) were retrieved from an occupational health register in the year following the survey. Baseline WAI scores were associated with LTSA episodes occurring (no/yes) during one-year follow-up by logistic regression analysis in a random sample (N=1000) of the cohort. Predictions of LTSA risk were then validated among the workers not included in the random sample. ' ' RESULTS ': 'The odds of LTSA episodes at follow-up decreased with increasing baseline WAI scores (ie, better work ability). The WAI accurately predicted the risk of future LTSA episodes >28, >42, >60 days, but over-predicted the risk of LTSA episodes >14 and >90 days. The WAI discriminated between workers at high and low risk of LTSA episodes of all durations. Office workers had higher WAI scores than manual workers. Consequently, false-negative rates were higher among office workers and false-positive rates were higher among manual workers at each WAI cut-off point. ' ' CONCLUSION ': 'The WAI could be used to screen both manual and office workers for risk of LTSA episodes lasting >28, >42, >60 days. WAI cut-off points depend on the objectives of screening and may differ for manual and office workers.
Keywords: absenteeism; calibration; discriminative ability; long-term sickness absence; manual worker; office worker; prognostic research; ROC analysis; screening; sensitivity; sick leave; specificity; WAI; work ability index; Youden index